Answer:
40
Step-by-step explanation:
A + B=75
A + C = 61
B = 5/3 *C
A+C * 5/3 = 75 then we got the answer
Answer:
(2, -1)
Step-by-step explanation:
We can add the first equation by the second
(4x + 6y = 2)+(-4x + 4y = -12)=
10y=-10
we divide both sides by 10 to get
y=-1
We plug -1 in the second equation to get:
-4x+4(-1)=-12
-4x-4=-12
-4x=-8
Now, we divide both sides by -4
x=2
Hope this helps!
Answer:
5
Step-by-step explanation:
If Wendy has $27 to buy seeds, and each seed bag costs $5, then:
5 · 5 = 25
5 · 6 = 30
27<30
27>25
So, Wendy is able to buy 5 bags and remain with 2 dollars.
Answer:
The solution is g = 4
Step-by-step explanation:
* 6(-2g - 1) = -(13g + 2)
- We need to solve it to find the value of g
- Let us simplify each side and then solve the equation
∵ 6(-2g - 1) = (6)(-2g) - (6)(1)
∴ 6(-2g - 1) = -12g - 6
∴ The simplify of 6(-2g - 1) is -12g - 6 ⇒ (1)
∵ -(13g + 2) = -13g - 2
∴ The simplify of -(13g + 2) is -13g - 2 ⇒ (2)
- Equate (1) and (2)
∴ -12g - 6 = -13g - 2
- Add 13g to both sides
∴ g - 6 = - 2
- Add 6 to both sides
∴ g = 4
* The solution is g = 4
Answer: n = -1 n = 3
Step-by-step explanation: